Linguistic Roots — Mother Tongues of Indian Children in South Africa - Naskar, Debjani (THE PRIMARY TEACHER, 2017)
‘Diaspora’ refers to historic mass dispersions of people with common roots, including ‘transnational community’ (people with a shared identity going beyond their national boundaries). Indians belonging to different communities form a sizeable segment in South Africa. Linguistic diversity has always been a defining feature of South Africa as the transnational flow of people is accompanied by a corresponding flow of languages. In fact, it is popularly known as the ‘Rainbow Nation’. This paper tries to analyse the issue of increasing levels of multilingualism and multiculturalism as a consequence of ongoing globalisation. It looks at the major challenges that the diasporic community living in South Africa faces. Specifically, the paper tries to examine a change in the country’s linguistic tapestry with the arrival of Indian diaspora, especially, policies of school education and their impact on the mother tongues of Indians living there, particularly, children.